Implementación biotecnológica en pacas digestoras. (2023)
This research work addressed the study of the construction of conventional biodigester bales and their characterization; where, long processing times of organic matter were identified, ranging from 10 to 12 months. This led us to propose the implementation of a biotechnological strategy, which would optimize the process of digester bales in terms of time and final product; for which a mixture of microorganisms specialized in the decomposition of organic matter from different sources was used. Managing to reduce the time of obtaining organic fertilizer to 4 months, improving the fixation of iron and other essential metals for plant nutrition, since the ash indicates the amount of minerals that were successfully fixed in the degradation process of organic matter. With this in mind, the biotechnological treatment is the most efficient in the fixation of inorganic minerals to the soil with an ash value of 29.29%, which allows them to present greater availability for plant nutrition. This result is complemented by the low volatilization loss value of 70.71%, which indicates that the biotechnological process increases the availability of micronutrients in their inorganic form. Additionally, the absence of pathogenic microorganisms in the final product is noteworthy.